Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2003
DOI: 10.1021/tx034053g
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Trivalent Arsenicals with Metallothionein

Abstract: Arsenic is a human carcinogen, causing skin, bladder, and lung cancers. Although arsenic in drinking water affects millions of people worldwide, the mechanism(s) of action by which arsenic causes cancers is not known. Arsenic probably exerts some toxic effects by binding with proteins. However, few experimental data are available on arsenic-containing proteins in biological systems. This study reports on arsenic interaction with metallothionein and established binding stoichiometries between metallothionein an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
81
0
1

Year Published

2005
2005
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(91 citation statements)
references
References 57 publications
9
81
0
1
Order By: Relevance
“…As-, MMA-, and DMA-MT2A Complexes Figure 5 shows the mass spectra of As 3ϩ , MMA, and DMA with MT2A. The maximum numbers of arsenic species bound by MT are: As 3ϩ , 6; MMA, 10; and DMA, 20; in accordance with previous observation [15]. The presence of the methyl groups affects binding with MT2A, which translates into changes in the crosssection.…”
Section: Ag- Cu- and Hg-mt2a Complexessupporting
confidence: 85%
See 3 more Smart Citations
“…As-, MMA-, and DMA-MT2A Complexes Figure 5 shows the mass spectra of As 3ϩ , MMA, and DMA with MT2A. The maximum numbers of arsenic species bound by MT are: As 3ϩ , 6; MMA, 10; and DMA, 20; in accordance with previous observation [15]. The presence of the methyl groups affects binding with MT2A, which translates into changes in the crosssection.…”
Section: Ag- Cu- and Hg-mt2a Complexessupporting
confidence: 85%
“…Take the 4ϩ ions, the As 6 MT2A complex has a cross-section of 750 Å 2 ; the MMA 10 MT2A complex, 800 Å 2 ; and the DMA 20 MT2A complex, 960 and 1150 Å 2 . The increase in cross-section from the As 3ϩ to MMA to DMA complex can be interpreted as a decrease in "cross-linking" (As 3ϩ binds to three cysteinyl S Ϫ , MMA two, and DMA only one) [15] and/or an increase in the cross-section of the individual arsenic species due to increasing number of methyl groups. Similarly, for the 6ϩ ions, the As 6 MT2A complex gives a cross-section of 790 Å 2 ; the MMA 10 MT2A complex, 920 Å 2 ; and the DMA 20 MT2A complex, 1220 Å 2 .…”
Section: Ag- Cu- and Hg-mt2a Complexesmentioning
confidence: 99%
See 2 more Smart Citations
“…Arsenic has been shown to induce MT expression both in vitro and in vivo [16][17][18]. Furthermore, Jiang et al reported that arsenic and its methylated metabolites interacted with MT in a stoichiometric fashion [16]. Recent evidence indicates that human populations poorly expressing MT may be more sensitive to chronic arsenic intoxication [19].…”
Section: Introductionmentioning
confidence: 99%